Varied Alignment Methods and Versatile Actuations for Liquid Crystal Elastomers: A Review - Jiayou Zhao; Limei Zhang; Jian Hu (Advanced Intelligent Systems, 2022)
Liquid crystal elastomers (LCEs) are a class of programmable polymer materials that can deform reversibly under diverse stimuli such as light, heat, electric field, and magnetic field. LCEs have demonstrated their potential applications in soft robots, soft actuators, artificial muscles, etc. How to align the mesogen orientation and achieve actuations of LCEs are the two most important issues for the studies on LCEs. At present, varied alignment methods and versatile actuations for LCEs have developed rapidly. However, few reviews are addressing these two important issues simultaneously. In this review, three types of alignment methods for LCEs as mechanical stress‐induced alignment, external field‐induced alignment, and surface effect‐induced alignment are summarized, and comparing their programmability toward the mesogen orientation is focused on. The key factors influencing the versatile actuations of LCEs are their orientation structure (intrinsic factor) and the applied external stimuli (extrinsic factor). Thus, actuations are classified into two types on the basis of programmable orientation structure and selective external stimuli, respectively, and focus on comparing their deformation controllability. Finally, an outlook for the future key technologies to develop versatile, precise, and fast‐responsive deformation actuations for LCEs is proposed.